Ø§Ù„ÙØ±ÙˆÙ‚ Ø§Ù„ÙÙ‚Ù‡ÙŠØ© ÙÙŠ ÙƒØªØ¨ ÙØ±ÙˆØ¹ Ø§Ù„Ù…Ø°Ù‡Ø¨ Ø§Ù„Ø´Ø§ÙØ¹ÙŠ - Akhmad Hanafi Dain Yunta; Awal Rifai Wahab (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2021)
Some fuqaha of syafiiyah in describing problems that have the same form but different laws which later became known as furuq fiqhiyyah, fuqaha of syafiiyah has been very prominent in describing furuq fiqhiyyah in the books of furu' mazhab. After reading some of the problems of furuq fiqhiyyah in some of these furu' books, the author finds that there is a difference between one writer and another in describing this furuq fiqhiyyah. Therefore, we need an initial article that explains the general guidelines about furuq fiqhiyyah. The author in this study uses the inductive deductive method by doing a general reading of several books of furu schools of syafiyyah, then concludes the method of describing their furuq fiqhiyyah. The conclusion that the authors get is that fuqaha of syafiiyah in describing furuq fiqhiyyah in the furu' mazhab book uses several categories: first: based on the mention of lafadz furuq used, second: based on the mention of he different sides of the two problems, third: based on the cause and background and the intention of furuq fiqhiyyah mentioned, fourth: based on the basis and origin of this furuq fiqhiyyah, and fifth: based on whether the two problems mentioned in this problem originate from one chapter of fiqh or come from different chapters